Implicit leadership theory : a study on the perception of military and private sector leaders by Singaporean undergraduates - Indahsuria Mokhtar (2011)
This study is built upon the recent study by Soh, Chan, Li, & Tay [2010] which presented findings on the Implicit Leadership Theory (ILT) of military personnel on military and private sector leaders in Singapore. This paper seeks to extend the understanding and generalisability of ILTs of outstanding military and private sector leaders to the undergraduate population. The undergraduate population is expected to present a new dimension to the ILT study conducted by Soh et al. [2010], which solely sampled military officers who have been greatly immersed in the military culture and leadership. The undergraduate population has a good mix of individuals with some military experience and working experience. By considering these inherent demographics, would the student sample yield similar or vastly different results from the military sample? By factoring in different demographics (gender and experiences) in Singapore, this study aims to explore the interrelating factors that in one way or another, affect the respondents’ perceptions of outstanding military and private sector leaders. These perceptions affect the respondents’ evaluation of the two types of leaders, whom they will often work with in their future careers or the period within which they engage in reservist to the army.